ANALISIS TITIK IMPAS VOLUME PRODUKSI PRODUK BATAKO DI RIBAS BATAKO KABUPATEN KUPANG - Bastianus Jawa; Paulina Y Amtiran; Wehelmina M Ndoen (Journal of Management Small and Medium Enterprises (SMEs), 2020)
This research was conducted at the Batako Ribas Batako in Kupang Regency. The purpose of this study was to determine the break-even point of production volume in a unit of brick products. The data used in this study are primary data which are production data for 2015-2019. The method used in this research is quantitative descriptive. The data analysis technique used in this study in this study is the break-even analysis. The results of this study are that brak-even analysis is still affective in increasing production volume because of the results of research and discussion found that increasing production volume can also increase revenue and profits for the company. The conclusion of this study is the Break-Even Point shown that the highest of batako products is in 2017, because in that year the production costs incurred were lower than the last two years. While the hignest profit rate is occurred in 2018 because the volume of the production is increased and the selling price is also increased. Keywords: Analysis, Profit, Production, Break Even Point, Production Volume